Mészáros and the need to supersede capital - Santos, Milena da Silva (Argumentum, 2022)
The text analyses István Mészáros’ theoretical concept, taken from his work “Beyond capital: towards the theory of transition”, regarding the need to supersede capital. The investigation adopted a materialist-historical and dialectical approach, with a Marxian basis, and employed a bibliographic methodology. It addresses issues related to the historical transience of capital, the relationship between capital, labour and State, and the alternative to capital. It considers the capitalist system as a triad composed of capital, labour, and State, which, like any sociability, is liable to be superseded by another social system which would cause a transition. Furthermore, it highlights aspects related to the Marxian socialist theory as an alternative for overcoming capital.